Long-Term Efficacy and Safety of Luspatercept for Anemia Treatment in Patients With Lower-Risk Myelodysplastic Syndromes: The Phase II PACE-MDS Study. Issue 33 (20th November 2022) - Platzbecker, Uwe; Götze, Katharina S.; Kiewe, Philipp; Germing, Ulrich; Mayer, Karin; Radsak, Markus; Wolff, Thomas; Chromik, Joerg; Sockel, Katja; Oelschlägel, Uta; Haase, Detlef; Illmer, Thomas; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co‐primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. Luspatercept has high clinical activity in patients with transfusion-dependent lower-risk myelodysplastic syndromes (LR-MDS) and ring sideroblasts (RS) relapsed or refractory to erythropoietin. We report long-term luspatercept safety and efficacy in 108 patients with LR-MDS in the PACE-MDS study, including 44 non-RS and 34 non–transfusion-dependent or previously untreated patients. The primary end point was safety. Secondary end points included rates of hematologic improvement (HI) erythroid (HI-E), HI neutrophil, and HI platelet. Exploratory end points included erythropoiesis biomarker quantitation and mutation data. Median duration of luspatercept exposure was 315 days (range, 21-1, 934 days). No new safety signals emerged. HI-E was observed in 53.7% of patients, including 36.4% of non-RS and 70.6% of non–transfusion-dependent patients. HI neutrophil and HI platelet were observed in 33.3% and 9.5% of patients, respectively. An almost three-fold increase in bone marrow late to early progenitor cell ratio accompanied HI-E response, irrespective of RS status. Lower baseline erythropoietin levels in non-RS patients (69.6 v 623.3 IU/L; P = .0077) and higher late to early erythroid progenitor cell ratio (10.44 v 4.48; P = .0106) in RS patients were associated with HI-E. This study highlights luspatercept's effects across LR-MDS subtypes, including untreated MDS-RS, serving as a platform for future trials.